Response of Gilthead Seabream (Sparus aurata L., 1758) Larvae to Nursery Odor Cues as Described by a New Set of Behavioral Indexes - Morais, Pedro; Parra, María P.; Baptista, Vânia; Ribeiro, Laura; Pousão-Ferreira, Pedro; Teodósio, Maria A. (Frontiers in Marine Science, 2017)
Temperate marine fish larvae use a series of environmental cues (e.g., olfactory, hearing, visual) to mediate the selection of nursery habitats. However, habitat selection may vary according to individuals’ physiological condition. Therefore, this study aimed to determine the ability of gilthead seabream (Sparus aurata L., 1758) larvae to utilize natural odor cues to locate nursery habitats along ontogeny and to examine how it varies with individual’s physiological condition. The hypothesis being tested is that Sparus aurata larvae prefer coastal rocky reefs as nursery areas, but they might use coastal lagoons as nursery grounds – ecosystems known for their productivity – if under starvation conditions, as a compensatory mechanism to avoid slow growth or even death. A choice-chamber experiment was used to investigate the behavioral responses of satiated and starved laboratory-reared Sparus aurata larvae, along ontogeny (pre-flexion, flexion, post-flexion), to water collected in a coastal artificial rocky reef and a coastal lagoon. The physiological condition of Sparus aurata larvae was determined by analyzing several biochemical condition indices. Complementarily, a new set of four preference indexes were developed – Choice-Chamber Preference Indexes – and discussed to provide a clear measure of the behavioral changes of a species along ontogeny by balancing all the behavioral choices made during the experimental trials, including the unresponsive behavior. A developmental threshold was identified at 24 days post-hatching, before which insufficient swimming capability disabled responsive behavior. Beyond this threshold, post-flexion larvae preferred rocky coastal water over lagoon water, even if under starvation conditions or poor physiological condition, despite the fact that the unresponsive behavior was largely predominant. Sparus aurata larvae displayed a cautionary behavioral strategy, so the compensatory mechanisms to ensure metapopulation stability and resilience have to rely on their feeding plasticity and on being a batch-spawning species (i.e., diversified bet-hedging strategy) to compensate the lack of apparent behavioral plasticity.